Transfer Equity for "Minoritized" Students: A Critical Policy Analysis of Seven States. (September 2014) - Chase, Megan M.; Dowd, Alicia C.; Pazich, Loni Bordoloi; Bensimon, Estela Mara
Using critical policy analysis focused on racial-ethnic equity, this study analyses state policy documents and accountability instruments governing transfer from 2-year colleges to 4-year institutions in the following states: California, Florida, Texas, Michigan, Minnesota, Washington, and Wisconsin. Based on data collected in 2009, the findings indicate that state transfer policies are largely "color blind." In contrast, accountability reporting, including data indicators such as those for underrepresented students, may serve as proxies for monitoring progress toward transfer of racially minoritized students. Recommendations are proposed for creating racially equitable state transfer policies and accountability instruments.